2016
DOI: 10.1098/rsos.160317
|View full text |Cite
|
Sign up to set email alerts
|

Seabird diving behaviour reveals the functional significance of shelf-sea fronts as foraging hotspots

Abstract: Oceanic fronts are key habitats for a diverse range of marine predators, yet how they influence fine-scale foraging behaviour is poorly understood. Here, we investigated the dive behaviour of northern gannets Morus bassanus in relation to shelf-sea fronts. We GPS (global positioning system) tracked 53 breeding birds and examined the relationship between 1901 foraging dives (from time-depth recorders) and thermal fronts (identified via Earth Observation composite front mapping) in the Celtic Sea, Northeast Atla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 93 publications
3
25
0
Order By: Relevance
“…Other studies have found that SST can predict seabird aggregations (Hyrenbach et al 2006, Nishizawa et al 2015, especially in frontal zones (Abrams 1985, Begg & Reid 1997, which was not the case in this study. In our study area, the average SST does not vary substantially during the period surveyed, and fronts driving prey distribution did not appear to be present, as documented in other areas (Hoefer 2000, Bost et al 2009, Scales et al 2014, Cox et al 2016. In contrast, capelin aggregate mostly near the seabed in a layer of > 0°C water within deep (> 200 m) trenches during their inshore spawning migration on the Newfoundland Shelf (Mowbray 2002) and then occupy depths with > 0°C water while inshore during the spawning season (Davoren et al 2006), suggesting that capelin distribution would be more correlated with bottom temperature than with SST.…”
Section: Discussionsupporting
confidence: 64%
“…Other studies have found that SST can predict seabird aggregations (Hyrenbach et al 2006, Nishizawa et al 2015, especially in frontal zones (Abrams 1985, Begg & Reid 1997, which was not the case in this study. In our study area, the average SST does not vary substantially during the period surveyed, and fronts driving prey distribution did not appear to be present, as documented in other areas (Hoefer 2000, Bost et al 2009, Scales et al 2014, Cox et al 2016. In contrast, capelin aggregate mostly near the seabed in a layer of > 0°C water within deep (> 200 m) trenches during their inshore spawning migration on the Newfoundland Shelf (Mowbray 2002) and then occupy depths with > 0°C water while inshore during the spawning season (Davoren et al 2006), suggesting that capelin distribution would be more correlated with bottom temperature than with SST.…”
Section: Discussionsupporting
confidence: 64%
“…The interactions between the tidal cycle and distance to the colony or depth might appear to explain relatively small amounts of model variance. However, they are comparable to the variance explained by oceanic fronts (Cox et al 2016), which are now widely accepted to be important features enhancing prey availability to marine top predators (Scales et al 2014, Cox et al 2016). Furthermore, for animals with such finely balanced energy budgets (Collins et al 2016), the fact that these behavioural changes occur repeatedly within central-place foraging suggests that the ability to adapt to predictable resource changes in otherwise variable environments could make all the difference between breeding success and failure.…”
Section: Discussionmentioning
confidence: 75%
“…In predictable environments, returning to previous foraging locations should be favoured; conversely, in unpredictable habitats the probability of a previous location being profitable again is low, and consequently, animals should show lower site fidelity and greater reliance on environmental cues to locate prey (Switzer, 1993;Weimerskirch, Le Corre, Jaquemet, & Marsac, 2005). The marine environment is characterized by both persistent oceanographic features (bathymetric structures and fronts) which generate predictable prey patches, as well as highly dynamic tidal and weather processes which result in spatiotemporally variable resource distributions (Cox et al, 2016;Scales et al, 2014). High and low reliance on environmental cues may represent alternative foraging tactics that can both be profitable within the same macro-scale habitat (Carroll, Harcourt, Pitcher, Slip, & Jonsen, 2018).…”
Section: Boldness and Foraging Site Fidelitymentioning
confidence: 99%